Sustainable dolphin watching tours as a tool to increase public awareness of marine conservation – a comparative analysis between two Mediterranean destinations and implications for management. Issue 4 (1st October 2020) - La Manna, Gabriella; Melis, Giuseppe; Rako-Gospić, Nikolina; Basta, Jelena; Mackelworth, Peter; Holcer, Draško; Atzeni, Marcello; Leeb, Katharina
ABSTRACT: Dolphin watching is growing fast along the Mediterranean coasts, without an equivalent effort for its management. Whale and dolphin watching has been promoted as ecotourism with conservation benefits. However, only a few studies have investigated the potential of these tours to change the awareness of the participants and improve their pro-conservation sentiments. In the present study, the motivation, interest, knowledge, expectations and satisfaction of the dolphin watchers were evaluated in two sites (Sardinia and Lošinj). The aim was to better address management strategies of dolphin watching in the Mediterranean Sea. Based on the questionnaires filled by the participants, the dolphin watchers in both destinations showed a generally high environmental awareness and sense of responsibility towards marine conservation. Moreover, awareness and responsibility increased after the experience. The results reveal that a carefully planned education would maximise the pro-environmental effects of the tours and minimise the impact on the target species.